Formative Assessment in Primary and Secondary Physical Education Classes From Novel Teachers’ Perspective - Cañadas, Laura; Santos-Pastor, María Luisa (Revista Electrónica Educare, 2021)
Aims. To value how formative assessment processes are used by novel teachers in physical education classes. Methods. A case study with four graduates (less than three years of teaching experience) was conducted; they have developed their teacher education in European Higher Education Area and currently teach in primary or secondary physical education classes. Information was collected through semi-structured interviews, non-participant observations, and documentary analysis. Results. The results show that systematic formative assessment processes are not carried out, although they introduce small changes in the assessment practices that give an alternative approach to the formative assessment, moving away from the traditional ways of assessment in physical education. In addition, the difficulty of adjusting all the elements of the assessment processes and making students see the importance and usefulness of these processes is highlighted in the first teaching years. Discussion. The results found in this study should serve as a reference to adjust the initial training to the needs and difficulties shown by novel teachers in order to facilitate their transition to the teaching profession in the application of formative assessment processes.